PENGARUH BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PADA MC DONALD’S DI PALMERAH JAKARTA BARAT - Deny Rumaidlany; Siti Mariam; Abdul Haeba Ramli (JURNAL LENTERA BISNIS, 2022)
This study aims to examine and analyze the effect of brand image and brand awareness on purchase decisions at Mc Donald's in Palmerah, West Jakarta. This study used a sample of 100 people who were selected using a non-probability sampling technique, namely the accidental sampling method. The dependent variable in this study is the purchase decision, while the independent variables are brand image and brand awareness. The results of this study indicate that brand image (X1) and brand awareness (X2) have a positive effect on purchase decisions (Y). It can be seen from the findings that: (1) brand image has a positive effect on purchase decisions with a value of 0.409 and a significance level of 0.000; (2) brand awareness has a positive effect on purchase decisions with a value of 0.586 and a significance level of 0.000; (3) brand image and brand awareness simultaneously have a positive effect on purchase decisions with an Fcount value of 91.46, greater than Ftable 3.09, and a significance value of 0.000 <0.05; and (4) the effect of brand image and brand awareness on purchase decisions is 65.3%, with the remaining 34.7% being the influence by other variables not examined in this study.Keywords: brand image, brand awareness, purchasing decisions, McDonald's